2016
DOI: 10.5430/jst.v7n1p16
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous isolated ipsilateral salivary gland metastasis from a primary breast cancer – A case report

Abstract: The most common sites of distant metastasis for breast are the lungs, liver, bones and brain. Here we report an extremely rare presentation of isolated salivary gland metastasis from primary breast cancer, indicating advanced stage of breast disease and sign of poor prognosis. The case emphasizes the need for a thorough workup for distant metastatic disease in patients diagnosed with invasive breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%
“…Our research strategy revealed a total of 88 relevant papers 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90…”
Section: Resultsmentioning
confidence: 99%